Integration and Evaluation of Corporate Social Responsibility (CSR) In Business Management - Syamsuri, Abd. Rasyid; Halim, Abd; Ikhlash, Muhammad (Pusat P2M Politeknik Negeri Batam, 2024)
Corporate social responsibility (CSR) is a moral endeavor that a business or organization does for the benefit of its stakeholders in order to enhance the company's reputation for contributing to the improvement of the quality of life and the environment. Objectives Achieving sustainable economic operations is directly tied to corporate social responsibility. The author used a qualitative methodology to analyze publications on CSR concerns and their life cycle in order to trace CSR. According to the investigation's findings, Indonesia implements CSR at a comparatively low rate when compared to other Asian nations. There are few CSR activities, but they frequently involve the exploitation of workers (poor pay, mistreatment), the environment (pollution, deforestation), and human rights. Although charity or philanthropic activities were a regular practice, CSR was a foreign idea for Indonesian businesses, which may have contributed to the poor penetration of CSR in Indonesia during the 1990s and early 2000s. In order to avoid losing credibility as a reaction to current challenges (2024 until the following year), CSR must be a top priority in company communications.